2014
DOI: 10.1155/2014/139219
|View full text |Cite
|
Sign up to set email alerts
|

The Global Burden of Road Injury: Its Relevance to the Emergency Physician

Abstract: Background. Road traffic crash fatalities in the United States are at the lowest level since 1950. The reduction in crash injury burden is attributed to several factors: public education and prevention programs, traffic safety policies and enforcement, improvements in vehicle design, and prehospital services coupled with emergency and acute trauma care. Globally, the disease burden of road traffic injuries is rising. In 1990, road traffic injuries ranked ninth in the ten leading causes of the global burden of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…These were studies conducted in response to the increase in road traffic accidents seen in Brazil and the importance of treating cardiac arrest immediately. Encouraging the adoption and implementation of these ideas in other LMICs would be beneficial to the health system as the global burden of road traffic accidents is concentrated in LMICs, and there is a growing morbidity and mortality trend due to cardiovascular diseases in LMICs 36 37. Similarly, these simulation-based initiatives can improve a country's ability to react to unforeseen threats or medical emergencies in order to deliver healthcare safely and handle outbreaks, especially after the recent Ebola crisis.…”
Section: Discussionmentioning
confidence: 99%
“…These were studies conducted in response to the increase in road traffic accidents seen in Brazil and the importance of treating cardiac arrest immediately. Encouraging the adoption and implementation of these ideas in other LMICs would be beneficial to the health system as the global burden of road traffic accidents is concentrated in LMICs, and there is a growing morbidity and mortality trend due to cardiovascular diseases in LMICs 36 37. Similarly, these simulation-based initiatives can improve a country's ability to react to unforeseen threats or medical emergencies in order to deliver healthcare safely and handle outbreaks, especially after the recent Ebola crisis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Emergency medical services (EMS), a system of ambulances and emergency departments (EDs) at hospitals, provide critical care for injured or ill patients before they are integrated into other health services. 4 However, there are several challenges to delivering high quality EMS care in sub-Saharan Africa, including patient overload, poor integration with other health services, limited and inefficient services, poor clinical documentation, and a shortage of physicians and necessary supplies. [5][6][7] The epidemiology of conditions presenting to the EMS needs to be studied to make efficient use of the scarce existing human, material and financial resources.…”
mentioning
confidence: 99%
“…(Ahmad, 2009)(Radin, 2006 This study has shown similar trend in the pre hospital and clinical parameters of the RTI victims to the nationwide and international data in particular data originating from the developing countries. (Chekijian, 2014) (Chalya, 2012) The victims commonly involved the young age group (40% at between 20 to 40 years of age), the age at which the general population is very productive socioeconomically. Male group contributed significantly to the motor vehicle crash (MVC) victims compared to the female counterpart.…”
Section: Discussionmentioning
confidence: 99%